HUBUNGAN ANTARA RASIO KREDIT BERMASALAH DENGAN RASIO PROFITABILITAS: Studi Empiris pada BPRse-Kota Tangerang Periode 2015 - Wibowo, Yohan Henri (Economic Faculty, Attahiriyah Islamic University, 2017)
The aims of this study is to find empirical evidence, that there is a significant relationship between the Non Performing Loan Ratio is reflected in indicators of Non-Performing Loan (NPL) with a Profitability Ratio that is reflected in the indicators Net Profit Margin (NPM).The collecting of data method is secondary sources from Quarterly Financial Report Rural Banks (hereinafter referred to as BPR) as the city of Tangerang. The sample in this study is BPRin Kota Tangerang are categorized as Micro, Small and Medium Enterprises (hereinafter referred to as SMEs). The hypothesis was tested by normality test and linear regression, The results of the study are not found empirical evidence that there is a significant relationship between Non-Performing Loan Ratios were reflected in NPL with Ratio Profitability indicators are reflected in indicators of NPM.These results indicate that required the mediating factor, namely the Contractual Interest Income from Loans and Expenses of Assets Allowance (hereinafter referred PPAPWD) Keywords: Non-Performing Loan, Net Profit Margin